2015
DOI: 10.1037/a0037646
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mitigation evidence, ethnicity, and SES on death penalty decisions by European American and Latino venire persons.

Abstract: The purpose of the research was to determine whether European American and Latino mock jurors would demonstrate bias in death penalty decision making when mitigation evidence and defendant ethnicity and socioeconomic status (SES) were varied. A total of 561 actual venire persons acted as mock jurors and read a trial transcript that varied a defendant's case information (mitigating circumstances: strong/weak, defendant ethnicity: European American/Latino, and defendant SES: low/high). European American jurors r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 85 publications
(127 reference statements)
0
13
0
Order By: Relevance
“…Studies that have branched out beyond Black–White comparisons have found that social class moderates discrimination outcomes for other ethnic groups as well. As one example, low social class Hispanics are likely to receive longer and harsher criminal sentences than middle or high social class Hispanics (Espinoza & Willis‐Esqueda, ; Esqueda, Espinoza, & Culhane, ). It could be that these effects can be applied to other marginalized racial group members who face low levels of social class.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have branched out beyond Black–White comparisons have found that social class moderates discrimination outcomes for other ethnic groups as well. As one example, low social class Hispanics are likely to receive longer and harsher criminal sentences than middle or high social class Hispanics (Espinoza & Willis‐Esqueda, ; Esqueda, Espinoza, & Culhane, ). It could be that these effects can be applied to other marginalized racial group members who face low levels of social class.…”
Section: Future Directionsmentioning
confidence: 99%
“…Hispanics (Espinoza & Willis-Esqueda, 2015;Esqueda, Espinoza, & Culhane, 2008). It could be that these effects can be applied to other marginalized racial group members who face low levels of social class.…”
Section: Broadening the Scope Of Race And Social Class Researchmentioning
confidence: 99%
“…Similarly, White mock jurors report greater endorsement of aggravators and lower endorsement of mitigators in cases with an African American (compared to White) defendant (Lynch & Haney, 2011). White mock jurors were also more punitive toward Latino defendants in cases with weak (vs. strong) mitigating evidence (Espinoza & Willis-Esqueda, 2015).…”
Section: Juror Decision-making and Capital Punishmentmentioning
confidence: 99%
“…Similarly, Latino defendants are more likely to be sentenced to death in capital punishment cases (Thomson, 1997). Experimental studies have shown that White jurors are biased against Latino defendants, compared to White defendants (Espinoza & Willis-Esqueda, 2008, 2015; Willis-Esqueda, Espinoza, & Culhane, 2008). White participants found the Mexican American defendant being perceived as being more responsible, being blamed more, and having their version of the events less likely to be believed, compared to the White defendant (Willis-Esqueda et al, 2008).…”
Section: Anti-latino Bias In Legal Contextsmentioning
confidence: 99%
“…Though attitudes towards the justice system have been widely investigated in areas such as the death penalty [23], influences of gender and race on juror decision making [24] [25] [26], and insanity [27], there have been no studies to date that relate attitudes towards the criminal system and comprehension of legal terminology [16]. If we are to accurately define how juror instructions contribute to accurate decision making by juror members, then we must rule out other possible explanations, namely the attitudes towards the legal system a juror brings with them in the first place.…”
Section: Juror Attitudesmentioning
confidence: 99%